2015
DOI: 10.1075/jlp.14.3.02pul
|View full text |Cite
|
Sign up to set email alerts
|

Integration in Flanders (Belgium) – Citizenship as achievement

Abstract: In this article we will show, with Flanders (Belgium) as a concrete case, how intertwined integration and citizenship discourses and policies have become in contemporary super-diverse societies. Flanders is a clear example of how integration is gradually being replaced by virtual or moral citizenship. The fact that (moral) citizenship has replaced integration, has as a consequence that the concept of citizenship has shifted, in a subtle way, from a dynamic and contextualized process, which shapes itself in dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 21 publications
1
0
0
1
Order By: Relevance
“…This structural marginalization might lead to complete education failures (Blommaert and Van Avermaet 2008). Immigrant youth language ability seems to be intertwined with notions of citizenship and integration within a linguistically divided society (Pulinx and Van Avermaet 2015;Clycq 2016). This is again consistent with the Quebec study, in which Anglophones reported significantly more discrimination than their bilingual or Francophone peers, in a similarly tense context around a language divide (Rousseau et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…This structural marginalization might lead to complete education failures (Blommaert and Van Avermaet 2008). Immigrant youth language ability seems to be intertwined with notions of citizenship and integration within a linguistically divided society (Pulinx and Van Avermaet 2015;Clycq 2016). This is again consistent with the Quebec study, in which Anglophones reported significantly more discrimination than their bilingual or Francophone peers, in a similarly tense context around a language divide (Rousseau et al 2018).…”
Section: Discussionsupporting
confidence: 73%
“…In Vlaanderen kan 2004 als een keerpunt beschouwd worden. Toen werd het onthaalbeleid dat gericht was op (economische) participatie afgelost door een inburgeringsbeleid dat de nadruk legt op de sociaal-culturele aspecten van integratie en inspanningen verwacht van de individuele nieuwkomer op het vlak van Nederlandse taalbeheersing, de kennis van de Vlaamse samenleving en de naleving van democratische waarden (Loobuyck & Jacobs, 2010;Adam, 2013;Pulinx & Van Avermaet, 2015). In de ogen van de radicaalrechtse partij Vlaams Belang gaat deze 'assimilationist revival' echter niet ver genoeg.…”
Section: Inleidingunclassified